2018
DOI: 10.1111/imj.13648
|View full text |Cite
|
Sign up to set email alerts
|

Burden of atrial fibrillation in Māori and Pacific people in New Zealand: a cohort study

Abstract: AF screening and stroke thromboprophylaxis in Māori and Pacific people could start below the age of 65 years in NZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
7
14
0
Order By: Relevance
“…This recommendation is supported by: the higher burden of AF antecedents at a younger age coupled with higher AF stroke risk factor prevalence. A similar conclusion was reached by another study of AF among Indigenous peoples [28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This recommendation is supported by: the higher burden of AF antecedents at a younger age coupled with higher AF stroke risk factor prevalence. A similar conclusion was reached by another study of AF among Indigenous peoples [28].…”
Section: Discussionsupporting
confidence: 87%
“…An increase in frequency of AF with age occurs in the general population [17] and other Indigenous populations including M aori and Pacific peoples residing in New Zealand [28]. However evidence regarding the magnitude of AF prevalence in older age among Indigenous people is conflicting [717].…”
Section: Discussionmentioning
confidence: 99%
“…While the risk of stroke after AF is higher for many indigenous peoples, comparative data on stroke incidence are limited. The risk of stroke (based on CHA 2 DS 2 ‐VASc scores) is reported to be twice as high in New Zealand for Māori and Pacific patients under 65 with AF as for non‐Māori/non‐Pacific patients. We found that the incidence of stroke (and its subtypes) was higher among Aboriginal than non‐Aboriginal patients with AF, particularly among patients under 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Even within HICs, pockets of social deprivation and poverty can produce disparities in OAC usage that may require a different approach. High AF risk at a younger age and low OAC utilization are seen in first nation peoples and minorities [170][171][172]. c. Strategies to increase OAC uptake and promote adherence and persistence, such as physician education, patient education, and enhanced health literacy Many of the strategies described in i to vii are equally applicable to risk-factor management and rate and rhythm control.…”
Section: B Implementation Of Oac Therapy For Non-valvular and Valvular Af In Hics And Lmicsmentioning
confidence: 99%
“…Even within HICs, pockets of social deprivation and poverty can produce disparities in OAC usage that may require a different approach. High AF risk at a younger age and low OAC utilization are seen in first nation peoples and minorities [ 170 171 172 ].…”
Section: Anticoagulant Therapy To Prevent Af-related Strokementioning
confidence: 99%